Legislative Shortcomings in Dealing with the Travel and Movement of the Custodian with the Child and its Repercussions on the Right to visit - Bachir, Radhia; Guerroudj, Raouf (Journal of Legal Studies and Researches, 2022)
The freedom of movement and travel was supposed not to be absolute with regard to custody this is according to Article 49 of it, as it retracts in front of other rights that enjoy more protection, especially the right to visit, which is affected by the travel of the custodian of the child. Absolute, a matter that did not receive much attention in the light of the Algerian legal system due to the scarcity of its texts, which are not sufficient to solve all the practical problems that are being raised about it.